2019
DOI: 10.1111/rec.12951
|View full text |Cite
|
Sign up to set email alerts
|

Seed depredation negates the benefits of midstory hardwood removal on longleaf pine seedling establishment

Abstract: Midstory hardwoods are traditionally removed to restore longleaf pine on fire‐excluded savannas. However, recent evidence demonstrating midstory hardwood facilitation on longleaf pine seedling survival has brought this practice into question on xeric sites. Also, midstory hardwoods could facilitate longleaf pine seedling establishment, as hardwood litter may conceal seeds from seed predators or improve micro‐environmental conditions for seedling establishment. However, little is known about these potential mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Also, our results indicate that any potential facilitative effects on seedling establishment created by midstorey retention are not affecting germinant density for either species (Wahlenberg, 1946; Louise Loudermilk et al, 2016; Prévosto et al, 2020). Similarly, neither species’ germinant density was statistically improved by proximity to Aristida stricta cover, as has been noted in previous studies (Miller et al, 2019; Willis et al, 2019). However, Aristida stricta cover had a biologically relevant positive effect on germination for both species, indicating that Aristida stricta was not impeding germination.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Also, our results indicate that any potential facilitative effects on seedling establishment created by midstorey retention are not affecting germinant density for either species (Wahlenberg, 1946; Louise Loudermilk et al, 2016; Prévosto et al, 2020). Similarly, neither species’ germinant density was statistically improved by proximity to Aristida stricta cover, as has been noted in previous studies (Miller et al, 2019; Willis et al, 2019). However, Aristida stricta cover had a biologically relevant positive effect on germination for both species, indicating that Aristida stricta was not impeding germination.…”
Section: Discussionsupporting
confidence: 83%
“…We suspect the selection for smaller‐seeded species was likely influenced by the local seed predator population. Although seed predator identity was not recorded in this study, small‐mammal abundance has been shown to be extremely low in frequently burned pine woodlands (Sasmal et al, 2017), and circumstantial evidence suggests that invertebrates are acting as the primary seed predators at our stand (Willis et al, 2019). Based on this assumption, the low occurrence of Quercus nigra granivory may be explained by the principles of optimal foraging theory, as foraging invertebrates may have avoided acorns due to their thick seed coat or size (Rey et al, 2002; Lichti et al, 2017).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations